User Centric Media Second International ICST Conference, UCMedia 2010, Palma de Mallorca, Spain, September 1-3, 2010. Revised Selected Papers - Alvarez, Federico; Costa, Cristina; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Conference, UCMedia 2010, which was held in Palma, Mallorca, Spain, in September 2010, accompanied by the 4th InterMedia Open Forum Workshop (IMOF). After a thorough review process 16 conference and 3 workshop papers were selected for inclusion in the book. The papers are grouped in topical sections on: personalised access to multimedia content; search and retrieval of networked multimedia content; multimedia, AMP, and user experience; video quality perception and user quality of experience; user generated content; content distribution; and content summarisation.
Personalised access to multimedia content -- search and retrieval of networked multimedia content -- multimedia, AMP, and user experience -- video quality perception and user quality of experience -- user generated content -- content distribution -- content summarisation.
Keywords: Computer science; Database management; Information storage and retrieval systems; Multimedia systems; Computer Science; Multimedia Information Systems; User Interfaces and Human Computer Interaction; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Media Design; Database Management